Progress in Fracture and Damage Mechanics. - Falzon, B. G. (Key engineering materials., 2008)
This special-topic volume reports on new progress made in the analysis and understanding of fracture and damage mechanics. The Finite Element Method is a well-established analytical tool for theoretical fracture analysis. The development of interface elements which combine aspects of both fracture and damage mechanics has permitted the prediction of both crack initiation and propagation. A number of the papers presented here deal with their use and further development. Substantial progress has also been made in the use of the Boundary Element Method for treating crack problems. The inherent ma.